2020
DOI: 10.2174/1871530320666200122155804
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Nickel-Induced Cell Damage in Allergic Contact Dermatitis and Nutritional Intervention Strategies

Abstract: Background: Hypersensitivity to nickel is a very common cause of allergic contact dermatitis since this metal is largely present in industrial and consumer products as well as in some commonly consumed foods, air, soil, and water. In nickel-sensitized individuals, a cell-mediated delayed hypersensitivity response results in contact dermatitis due to mucous membrane coming in long-term contact with nickel-containing objects. This process involves the generation of reactive oxidative species and lipid peroxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Meanwhile, hyperuricemia is closely linked to insulin resistance and increased oxidative stress in the liver. It is also involved in the development and progression of NAFLD [ 15 ], and the toxic mechanism of Ni was also attributed to this [ 53 ] These findings are consistent with our current results, suggesting that serum Ni is a risk factor for NAFLD. In addition, animal studies suggested that Ni-activating lipid peroxidation and the overproduction of free radicals causes severe hepatotoxicity, renal toxicity, and cytotoxicity, which in turn leads to elevations of uric acid and elevations in the ASAT and ALAT activities in male rats [ 54 , 55 , 56 , 57 ].…”
Section: Discussionsupporting
confidence: 91%
“…Meanwhile, hyperuricemia is closely linked to insulin resistance and increased oxidative stress in the liver. It is also involved in the development and progression of NAFLD [ 15 ], and the toxic mechanism of Ni was also attributed to this [ 53 ] These findings are consistent with our current results, suggesting that serum Ni is a risk factor for NAFLD. In addition, animal studies suggested that Ni-activating lipid peroxidation and the overproduction of free radicals causes severe hepatotoxicity, renal toxicity, and cytotoxicity, which in turn leads to elevations of uric acid and elevations in the ASAT and ALAT activities in male rats [ 54 , 55 , 56 , 57 ].…”
Section: Discussionsupporting
confidence: 91%
“…Drinking water and food are the two main sources of Ni exposure in humans and animals [8]. The environmental exposition of Ni induced the toxic effects in various organs [9,10], such as immunotoxicity [11], and genotoxicity [12]. Ni intoxication results in loss of body weight and respiratory disorders, increased serum levels of kidney function biomarkers indicating the development of kidney failure [13].…”
Section: Introductionmentioning
confidence: 99%
“…In their review on this issue, Roth‐Walter et al 38 described that: “Fe deficiency affects more T‐helper (Th)1 than Th2 immune cells,” that is, the “proliferative phase of T cells is dependent on Fe supply” and “Th1‐associated cytokines IFN‐y and the IL‐12/IL18‐mediated proliferation was found to be severely affected by iron chelators.” Conversely, it might be possible that this is balanced by normal Fe homeostasis. Filatova et al reported on another aspect, stating that a nutritional intervention with a diet sufficient in ion Fe might reduce enteral Ni absorption, thus potentially resulting in positive effects in Ni‐allergic individuals 39 . However, we do not know whether the rather high frequency of Fe supplementation within the Fe‐sensitized individuals is of any relevance in this context.…”
Section: Discussionmentioning
confidence: 84%
“…Filatova et al reported on another aspect, stating that a nutritional intervention with a diet sufficient in ion Fe might reduce enteral Ni absorption, thus potentially resulting in positive effects in Ni-allergic individuals. 39 However, we do not know whether the rather high frequency of Fe supplementation within the Fe-sensitized individuals is of any relevance in this context.…”
Section: Association Analysis and Further Characteristics Of The Fe-s...mentioning
confidence: 96%